Computed tomography-measured adipose tissue attenuation and area both predict adipocyte size and cardiometabolic risk in women. (3rd February 2016) - Côté, Julie Anne; Nazare, Julie-Anne; Nadeau, Mélanie; Leboeuf, Mathieu; Blackburn, Line; Després, Jean-Pierre; Tchernof, André
Abstract: Objective : To assess the ability of CT-derived measurements including adipose tissue attenuation and area to predict fat cell hypertrophy and related cardiometabolic risk.Methods: Abdominal adipose tissue areas and radiologic attenuation were assessed using 4 CT images in 241 women (age: 47 years, BMI: 26.5 kg/m 2 ). Fat cell weight was measured in paired VAT and SAT samples. Fasting plasma lipids, glucose and insulin levels were measured.Results : Adipose tissue attenuation was negatively correlated with SAT (r=-0.46) and VAT (r=-0.67) fat cell weight in the corresponding depot (p<0.0001 for both). Women with visceral adipocyte hypertrophy had higher total-, VLDL-, LDL- and HDL-triglyceride and apoB levels as well as a higher cholesterol/HDL-cholesterol ratio, fasting glucose and insulin levels compared to women with smaller visceral adipocytes. Adjustment for VAT area minimized these differences while subsequent adjustment for attenuation eliminated all differences, with the exception of fasting glycaemia. In SAT, adjustment for VAT area and attenuation eliminated all adipocyte hypertrophy-related alterations except for fasting hyperglycaemia.Conclusion : CT-derived adipose tissue attenuation and area both contribute to explain variation in the cardiometabolic risk profile associated with the same biological parameter: visceral fat cell hypertrophy.